Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV. Bhakti Insan Persada - Muhamad Umar Fahad; Asep Erik Nugraha; Sukanta Sukanta (Jurnal Ilmiah Wahana Pendidikan, 2021)
From the initial survey, it is known that weaknesses in employee performance are seen from the high level of employee absenteeism which can affect company performance. The problems studied are how motivation, work environment and employee performance, is there any influence of motivation and work environment on employee performance partially or simultaneously. The data collection methods used were questionnaires and documentation. The data analysis method used in this research is the percentage description analysis method and multiple linear regression. Based on the research results, it is obtained multiple linear regression equation Y = 24.493 + 0.181 X1 + 0.128 X2. By using SPSS 25 Hypothesis F test results show F count = 8,282 with a significance value = 0.001 <0.05, which means that H3 which reads "There is a significant effect of motivation and work environment on the performance of CV employees" accepted. Meanwhile, from the partial hypothesis test (t test), the t count of the motivation variable is 1.991, the work environment variable is 1.739 where the probability is smaller than 0.05, the hypothesis is accepted. The coefficient of determination (Adjusted R2) is 0.392, this means that 39.2% of employee performance is influenced by motivation and work environment, while the rest is influenced by other variables that are outside the variables examined in this study.